Applications of environmental DNA for marine biodiversity monitoring in Sumberkima Village, Bali, Indonesia - I NYOMAN DODIK PRASETIA; JASMINE MASYITHA AMELIA; GRESSTY SARI BR SITEPU; MADE DWIPA KUSUMA MAHARANI; DEWI WULANDARI; EGHBERT ELVAN AMPOU; MUHAMMAD DANIE AL MALIK; NINING NURSALIM; NENIK KHOLILAH; NI KADEK DITA CAHYANI (Society for Indonesian Biodiversity, 2025)
Abstract. Prasetia IND, Amelia JM, Sitepu GSB, Maharani MDK, Wulandari D, Ampou EE, Malik MDA, Nursalim N, Kholilah N, Cahyani NKD. 2025. Applications of environmental DNA for marine biodiversity monitoring in Sumberkima Village, Bali, Indonesia. Biodiversitas 26: 3939-3951. Sumberkima Village in North Bali, Indonesia, is known for its high marine diversity, yet it increasingly faces ecological stress from fishing and tourism activities. This study aims to assess the biodiversity of coral reef ecosystems in Sumberkima using a combination of visual census and environmental DNA (eDNA) metabarcoding. A Line Transect Method was conducted through SCUBA for a visual census to detect coral diversity and coral cover. Then, eDNA samples were collected from three stations (i) coral reef ecosystems, (ii) the transitional zone between seagrass and coral reef ecosystems, and (iii) coral reef ecosystems near the bay close to the mainland and analyzed using the COI locus to detect invertebrates and vertebrates. Seawater was taken for 1 L per station. A total of 200,709 reads and 662 Amplicon Sequence Variants (ASVs) of Eukaryotes, enabling the detection of cryptic and hard-to-observe species. Meanwhile, visual census using the Line Transect Method assessed coral diversity and cover, identifying 39 genera with conditions ranging from poor to medium. The integration of eDNA with traditional visual census techniques provides a more comprehensive biodiversity assessment, particularly in ecologically rich yet threatened marine environments such as Sumberkima, North Bali, Indonesia.